Decarboxylative ipso Amination of Activated Benzoic Acids. (17th December 2018) - Pichette Drapeau, Martin; Bahri, Janet; Lichte, Dominik; Gooßen, Lukas J.
Abstract: In the presence of a bimetallic Pd/Cu system with 1, 10‐phenanthroline as the ligand and either air or N ‐methylmorpholine N ‐oxide as the oxidant, electron‐deficient benzoic acids undergo oxidative decarboxylative coupling with unprotected amines. This operationally simple aniline synthesis is widely applicable with respect to the amine and gives good yields, even on multigram scale. The orthogonality of this reaction to other Pd‐catalyzed cross‐couplings allows the concise synthesis of multisubstituted arenes by sequential C−C, C−Cl, and C−N functionalizations. Mechanistic investigations suggest the intermediacy of a hypervalent Pd species.